Pathological Findings of Post-Viral Olfactory Dysfunction: A Systematic Review - Filip Hacksell; Amanj Saber (European Journal of Rhinology and Allergy)
Abstract: The coronavirus disease 2019 pandemic has shed light on the post-viral olfactory dysfunction (PVOD). Post-viral olfactory dysfunction is temporary for most people and usually subsides when the common cold symptoms ameliorate. However, in some patients, this condition can persist for several weeks or months. The exact pathological mechanisms of persistent olfactory loss secondary to upper respiratory tract infection (URTI) is unknown, and there is a lack of efective treatment. An increased understanding of pathology could possibly translate into new therapeutic regimens. The aim of this systematic review is to synthesize primary data regarding histopathological and neuropathological fndings in patients with PVOD secondary to URTI. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines was followed. Databases PubMed and Web of Science were searched with keywords and mesh terms to identify relevant articles. The quality of included studies was assessed with the Newcastle–Ottawa Scale for observational studies. The search yielded a total of 847 articles, after excluding duplicates and articles that were not relevant. A total of 12 studies were selected. The main fndings of this review were: olfactory bulb (OB) volume was decreased in patients with PVOD, there was a negative correlation between OB volume and duration of olfactory loss, both primary and secondary olfactory cortex changes were found in terms of structure and functionality, and the olfactory sensory neurons and nerve bundles were reduced in patients with PVOD. The mechanisms of PVOD are complex. This review found that viral URTI is attributable to structural and functional changes at multiple locations of the olfactory system.